PERMAINAN KARTU ION SOLUSI MENULISKAN RUMUS KIMIA SENYAWA ION DI KELAS X MAN 1 KOTA CILEGON - MARYATI MARYATI (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2023)
The purpose of compiling this best practice is to describe the methods and results of using the ion card game as a solution for writing the chemical formulas of compounds in class X. The steps taken by the author in compiling this best practice are: 1) Make ion cards with the required number; 2) Explain to students how to use ion cards; 3) Count the number of cation cards and anion cards; 4) Ask students to write chemical formulas in the form of AxBy; 5) Asking students to communicate the results of their group work; 6) Conduct tests to test competency achievement. By using the ion card game, from the two X MIPA classes, 95% of the students could write chemical formulas. Through the ion card game, writing down chemical formulas which are abstract materials and a prerequisite for other materials, turns out to be easier to understand. The students feel happy with this media, 86.75% actively participate in learning. Based on the success of the ion card game in these two classes, it is recommended that the ion card game be developed in madrasas or other schools in writing chemical formulas, nomenclature and chemical reaction equations. The obstacles in this activity are very minimal, students can even make their own ion cards from makeshift materials ABSTRAKTujuan penyusunan best practice ini adalah mendeskripsikan cara dan hasil menggunakan permainan kartu ion sebagai solusi untuk menuliskan rumus kimia senyawa di kelas X. Langkah-langkah yang dilakukan penulis dalam menyusun best practice ini adalah: 1) Membuat kartu ion dengan jumlah sesuai kebutuhan; 2) Menjelaskan kepada siswa cara menggunakan kartu ion; 3) Menghitung jumlah kartu kation dan jumlah kartu anion; 4) Meminta siswa menuliskan rumus kimia dalam bentuk AxBy; 5) Meminta siswa untuk mengkomunikasikan hasil kerja kelompoknya; 6) Melakukan tes untuk menguji ketercapaian kompetensi. Dengan menggunakan permainan kartu ion, maka dari dua kelas X MIPA sebanyak 95% siswa bisa menuliskan rumus kimia. Melalui permainan kartu ion, menuliskan rumus kimia yang merupakan materi abstrak dan menjadi prasyarat materi lainnya, ternyata menjadi lebih mudah dipahami. Para siswa merasa senang dengan media ini, 86,75% mengikuti pembelajaran dengan aktif. Atas dasar keberhasilan permainan kartu ion di dua kelas ini, maka direkomendasikan permainan kartu ion bisa dikembangkan di madrasah atau sekolah lain dalam menuliskan rumus kimia, tata nama dan persamaan reaksi kimia. Hambatan dalam kegiatan ini sangat minim, bahkan siswa bisa membuat sendiri kartu ion dari bahan seadanya